A qualitative study on the promotion and obstacle factors of pre rehabilitation for patients with degenerative lumbar spine disease based on virtual reality technology (基于虚拟现实技术的退行性腰椎疾病患者预康复促进和障碍因素的质性研究) - WANG Xiaoying (王小影); GAO Nana (高娜娜); GUO Jingran (郭敬然); MENG Xiaona (孟小娜); HU Huiju (胡惠菊) (中西医结合护理)
Objective The purpose of this study is to explore the promotion and obstacle factors of virtual reality technology in the pre-rehabilitation application of degenerative lumbar spine diseases. Methods The method is based on the Comprehensive Framework for Implementation Research (CFIR) and adopts a qualitative research method. Through purposive sampling, semi-structured interviews were conducted with 10 patients and 5 nurses using virtual reality devices in The Second Hospital of Tangshan, and the interview content was analyzed. Results The promoting factors for the implementation of pre-rehabilitation projects based on virtual reality technology in patients with degenerative lumbar spine diseases include relative advantages in innovation and communication in internal feature areas, urgency for change, and compatibility with existing workflows; Obstacle factors include innovation costs, design quality, and packaging in the field of innovation, collaborative relationships in external feature factors, incentive systems, and accessibility of knowledge and information in internal feature areas; Neutral factors include locations in the internal feature domain, implementation facilitators in the individual feature domain, and feedback and evaluation in the implementation process domain. Conclusion Virtual reality technology can promote better implementation of pre-rehabilitation for degenerative lumbar spine diseases, thereby reducing perioperative kinesiophobia, alleviating pain, and promoting rapid recovery; But it is important to choose appropriate and comfortable equipment to provide personalized, diversified, and gamified rehabilitation programs to overcome its obstacles. (目的 探讨虚拟现实技术在退行性腰椎疾病预康复中应用的促进和障碍因素。方法 以实施性研究综合框架(CFIR)为理论基础, 采用质性研究方法, 通过目的抽样, 对唐山市第二医院脊柱科10名应用虚拟现实设备的患者和5名护士进行半结构式访谈, 并对访谈内容进行分析。结果 基于虚拟现实技术预康复项目在退行性腰椎疾病患者中实施的促进因素包括创新领域中的创新相对优势及内部特征领域中的沟通、变革的迫切性和与现有工作流程相符的兼容性; 障碍因素包括创新领域中的创新成本及设计质量和包装, 外部特征因素领域的协作关系, 内部特征领域中的激励制度及知识和信息的可及性; 中性因素包括内部特征领域中的场所, 个体特征领域中的实施促进者, 实施过程领域中的反馈与评价。结论 虚拟现实技术可以促进退性腰椎疾病预康复更好的实施, 从而降低患者围手术期恐动程度, 减轻疼痛, 促进快速康复; 但要选择合适舒适的设备提供个性化、多元化、游戏化的康复项目以克服其障碍因素。)